Warunkowe zawieszenie wykonania kar jednostkowych i kary łącznej (na marginesie uchwały siedmiu sędziów Sądu Najwyższego z dnia 21 listopada 2001 r., I KZP 14/01) - Harasimowicz, Marcin (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
The major topic of the article is the outcome of the amendment of February 20, 2015, to Article 89 § 1 of the Polish Criminal Code. The author presents critical remarks to the position expressed by the Supreme Court in the resolution of November 21, 2001.